Central serotonin2B receptor blockade inhibits cocaine-induced hyperlocomotion independently of changes of subcortical dopamine outflow. (October 2015) - Devroye, Céline; Cathala, Adeline; Di Marco, Barbara; Caraci, Filippo; Drago, Filippo; Piazza, Pier Vincenzo; Spampinato, Umberto
Abstract: The central serotonin2B receptor (5-HT2B R) is currently considered as an interesting pharmacological target for improved treatment of drug addiction. In the present study, we assessed the effect of two selective 5-HT2B R antagonists, RS 127445 and LY 266097, on cocaine-induced hyperlocomotion and dopamine (DA) outflow in the nucleus accumbens (NAc) and the dorsal striatum of freely moving rats. The peripheral administration of RS 127445 (0.16 mg/kg, i.p.) or LY 266097 (0.63 mg/kg, i.p.) significantly reduced basal DA outflow in the NAc shell, but had no effect on cocaine (10 mg/kg, i.p.)-induced DA outflow in this brain region. Also, RS 127445 failed to modify both basal and cocaine-induced DA outflow in the NAc core and the dorsal striatum. Conversely, both 5-HT2B R antagonists reduced cocaine-induced hyperlocomotion. Furthermore, RS 127445 as well as the DA-R antagonist haloperidol (0.1 mg/kg, i.p.) reduced significantly the late-onset hyperlocomotion induced by the DA-R agonist quinpirole (0.5 mg/kg, s.c.). Altogether, these results demonstrate that 5-HT2B R blockade inhibits cocaine-induced hyperlocomotion independently of changes of subcortical DA outflow. This interaction takes place downstream to DA neurons and could involve an action at the level of dorsostriatal and/or NAc DA transmission, in keeping with the importance of these brain regions in the behavioural responses of cocaine. Overall, this study affords additional knowledge into the regulatory control exerted by the 5-HT2B R on ascending DA pathways, and provides additional support to the proposed role of 5-HT2B Rs as a new pharmacological target in drug addiction. Highlights: Cocaine-induced striatal and accumbal DA outflow is unaltered by 5-HT2B R blockade. Cocaine-induced hyperlocomotion is inhibited by 5-HT2B R blockade. Quinpirole-induced late-onset hyperlocomotion is inhibited by 5-HT2B R blockade. 5-HT2B Rs could control cocaine-hyperlocomotion by acting downstream to DA neurons.